Digital innovations as the basis for the implementation of the Concept for the development of T-shaped skills in higher education - Simanskiene, Ligita; Zuperkiene, Erika; Mishenina, Halyna (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
In the digital age, higher education is evolving to equip students with versatile T-shaped skills, combining deep expertise and broad knowledge. A research question was held: how do digital innovations play a pivotal role in nurturing T-shaped skills within higher education, considering the dynamic job market? The research methods used were an extensive literature review, best practice analysis, thematic studies, document analysis, data systematisation, generalisation, and modeling using the Mermaid tool. Findings emphasise the essential role of digital innovations in higher education, promoting T-shaped specialists. Key takeaways underscore the impact of digital learning, continuous assessment, and emerging technologies like the Metaverse. The article highlights the transformative potential of digital innovations in higher education, with a focus on strategic planning, resource allocation, and proactive measures. It provides comprehensive insights into digital innovation’s role in shaping T-shaped skills and calls for future longitudinal and contextual research.